Physiological Response to the 6-Minute Frame Running Test in Children and Adults With Cerebral Palsy. Issue 4 (5th October 2022) - Edelman Bos, Arnoud M. M.; Hjalmarsson, Emma; Dallmeijer, Annet J.; Fernandez-Gonzalo, Rodrigo; Buizer, Annemieke I.; Pingel, Jessica; Pontén, Eva; von Walden, Ferdinand; van Schie, Petra E. M.
Abstract : Purpose: To determine the physiological response and association to peak oxygen uptake of the 6-minute Frame Running test (6-MFRT) in persons with cerebral palsy (CP). Methods: Twenty-four participants with CP, Gross Motor Function Classification System II/III/IV, performed the 6-MFRT. Distance, peak heart rate (HRpeak ), peak respiratory exchange ratio (RERpeak ), and peak oxygen uptake (V ˙ O2peak ) were measured. Results: HRpeak ranged from 146 to 201 beats per minute, RERpeak from 0.94 to 1.49, 6-MFRT distance from 179 to 1220 m and V ˙ O2peak from 0.62 to 2.18 L/min. HRpeak was achieved in 63%, RERpeak in 71%. A strong correlation was observed between 6-MFRT and V ˙ O2peak . Conclusions: The 6-MFRT represented a (near) maximum effort for 75% of the participants and the 6-MFRT can be used to estimate oxygen consumption on an individual basis.